TRAINING PELATIHAN MEMBUAT BENTO YANG SEHAT DAN MENARIK BAGI IBU-IBU PKK DI DESA PANDAU PROVINSI RIAU : MEMBUAT BENTO YANG SEHAT DAN MENARIK BAGI IBU-IBU PKK DI DESA PANDAU PROVINSI RIAU - -, Putri Rahayuningtyas (Universitas Negeri Surabaya, 2024)
Abstract A lunch is a meal put into a box or container that makes it easy to take anywhere. In Japan, the term lunch is called bento. Bento is a rice lunch that is usually carried by the Japanese people since ancient times until now, for housewives, this bento is a common thing for them, even this bento is made every day as a family supply whether it is the office, school and picnic. So in the lives of Japanese people, and this has become a tradition or habit of the Japanese people. This healthy and attractive bento can make children interested in bringing it to school. Therefore, it is necessary to hold training to make healthy and attractive bento to PKK in Pandau Jaya. The method used is the training method, starting with the introduction of a typical Japanese bento starting from the history, the ingredients needed for making bento. After that, training to make healthy and attractive bento based on the standard contents of my plate. From the evaluation results, 68% of participants were interested in knowing how to make bento and 64% of participants were interested in knowing healthy and attractive bento. However, only 24% of the participants were interested and motivated to open a business through bento making. Suggestions that participants want this activity to be sustainable with other training in the field of Japanese cuisine such as the introduction of traditional Japanese food and cakes. Keywords: bento, luch, Japan, healthy, atttactive